Computerized Circuit and Raceway Management - Meehan, W. J.; Bates, J. F.; Mulgrew, J. E. (IEEE transactions on power apparatus and systems, 1980)
A significant amount of time and effort is spent on circuit scheduling and cable routing through electric raceways during the electrical design of large power plants. Manual methods are costly, exceedingly time-consuming, and are subject to numerous human inaccuracies. Computer programs have been developed to replace manual methods. However, the amount of data preparation and data handling required for computerized circuit scheduling and cable routing is still massive and subject to errors and inconsistencies without proper data management.